(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
Rock music and acetabular society are a contentious place within modern culture, with individuals of the dominant mainstream typically stigmatizing them as an outgrowth of intrinsic gang as well as drug culture. Popular music and hip-hop movement occupy a contentious territory in modern American society. But in the other hand, this dismissal ignores the complicated political, socioeconomic, and geopolitical factors that have influenced the development and expansion of this form of creative expression. This essay argues that rock music is a resistant profession that allows disenfranchised Black American adolescents to express views and concerns that are frequently ignored by the dominant cultural, but that it therefore contributes significantly to Black American personalities and culture. The authors critically investigate the concept of "culture" in cognitive science, misinterpreting it via a postmodern lens that considers the influence of control, domination, and rejection in culture production. In order to support that viewpoint.